Faktor-Faktor yang Mempengaruhi Kepatuhan Penggunaan Alat Pelindung Diri pada Pekerja Konstruksi - Puspa Dewi, Virda; Susilawati, Susilawati (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2024)
In Indonesia, there were 130,923 work accidents, most of which occurred on construction projects. The source is data from the 2019 Ministry of Public Works and Spatial Planning Construction Development. One of the causes of accidents is non-compliance with the use of PPE. This research aims to determine and understand the factors associated with non-compliance with using PPE for construction workers. This research uses a literature review method using Google Scholar as an electronic data source. Journal publications starting from 2019-2023 are used with the keywords: compliance factors, PPE, and construction. Age, length of service, attitude and knowledge, motivation to work, compensation and punishment, and availability of PPE can influence construction worker compliance. In the use of PPE for employees, four factors relate to compliance: enablers, predispositions, drivers, and individuals. This is very important, so it is hoped that wider knowledge about the use of PPE will increase. Contractors must also supervise, communicate and ensure that PPE is available so that workers are more compliant in using it in the future and the level of work accidents can be reduced.